Arthritis of the large joints—in particular, the knee—at first presentation is predictive for a high level of radiological destruction of the small joints in rheumatoid arthritis. Issue 5 (1st December 2006) - Linn-Rasker, S P; van der Helm-van Mil, A H M; Breedveld, F C; Huizinga, T W J
Abstract : Objective: To investigate the predictive value of the distribution of inflamed joints at first presentation for the severity of the disease course in rheumatoid arthritis (RA). Methods: Of the 1009 consecutive patients included in the Leiden Early Arthritis Clinic (Leiden, The Netherlands), 285 patients fulfilled the American College of Rheumatology criteria for RA within 1 year of follow-up. Of these, 28 patients achieved remission. Radiographs of hands and feet were scored according to the Sharp–van der Heijde method, and the 28 patients with the most destructive disease were selected. The distribution of inflamed joints of the patients with the extreme disease courses was compared. The association between the distribution of inflamed joints and the level of destruction of the joints of hands and feet in the whole group of patients with RA was assessed using regression analysis. Results: Comparison of patients with extreme disease courses using univariate and logistic regression analyses showed that arthritis of the large joints—in particular, the knee—was associated with severe RA. In the whole group of patients with RA, the total number of swollen joints and the presence of knee arthritis were associated independently with the level of destruction of the small joints. Patients with RA with knee arthritis had higher C reactive protein (CRP) levels than patients without knee arthritis, and investigating the distribution of inflamed joints together with other variables yielded the number of swollen joints, CRP, presence of anti-cyclic citrullinated peptide antibodies and symptom duration as predictors for severity of RA. Conclusion: Arthritis of large joints—in particular, the knee—at first presentation is associated with a destructive course of RA.